SIMULASI DAN ANALISIS INJEKSI PLASTIK BESERTA OPTIMASI BERBASIS SOFTWARE CAE UNTUK PRODUK KOMPONEN KELISTRIKAN - Arif Budi Wicaksono; Reyhan Aziz Zuliansyah; Santo Ajie Dhewanto; Muhammad Iwan Nur Fauzan (P3M Politeknik Negeri Indramayu, 2024)
The research focuses on the simulation and analysis of injection molding of electrical components that can be carried out by the manufacturing process. The design of the electrical components has been made so it is necessary to follow up on the design for an injection molding simulation. The injection parameters including injection pressure, clamp open time, mold temperature, and melt temperature are fixed, but if the results are less than optimal then changes to the fixed parameters can be made. Changes to the cavity layout and gating system are varied to find out how much influence it has on product results and to find the most optimal results from the simulations that have been done. In the simulation results section, if there is a short-shot defect, the result cannot be taken into account in the simulation results for analysis. The most optimal injection simulation results from inbow electrical terminal components with automatic timer modules made by design molds.